Coworking Spaces as a Driver of the Post-Fordist City: a Tool for Building a Creative Ecosystem - Bednář, Pavel; Danko, Lukáš (European Spatial Research and Policy, 2020)
Collaborative places nurture creativity and efficiency of cultural and creative industries. Research in collaborative places revealed they are essential for networking and cooperation in the creative ecosystem. The results of studies focusing on competitiveness of coworking spaces and their effect on boosting entrepreneurship are rather vague. Furthermore, an awareness of how coworking spaces stimulate coworkers to engage in urban regeneration through local community initiatives is limited. Hence, this study seeks to provide an insight into coworking spaces from the organizational perspective devoted to entrepreneurship and competitiveness. Simultaneously, the paper aims to reveal synergies between creative communities and local development. The method of data gathering consists of semi-structured in-depth interviews with managers and entrepreneurs from selected countries of the EU applying the grounded theory for their analysis. The results suggest that coworking spaces indicate a boosting of the entrepreneurship of the creative class through collective projects. These activities tend to stimulate knowledge creation and open innovation in the creative ecosystem that benefit local development. Coworking spaces also represent a driving force to initiate and maintain a dialogue between the creative ecosystem and local authorities for culture-led urban development.